Comparison of American and European practices in the management of patients with primary immunodeficiencies. - Hernandez-Trujillo, H; Chapel, H; Lo Re, V; Notarangelo, L; Gathmann, B; Grimbacher, B; Boyle, J; Hernandez-Trujillo, V; Scalchunes, C; Boyle, M; Orange, J (2012)
Primary immunodeficiency diseases (PIDs) comprise a heterogeneous group of rare disorders. This study was devised in order to compare management of these diseases in the northern hemisphere, given the variability of practice among clinicians in North America. The members of two international societies for clinical immunologists were asked about their management protocols in relation to their PID practice. An anonymous internet questionnaire, used previously for a survey of the American Academy of Allergy, Asthma and Immunology (AAAAI), was offered to all full members of the European Society for Immunodeficiency (ESID). The replies were analysed in three groups, according to the proportion of PID patients in the practice of each respondent; this resulted in two groups from North America and one from Europe. The 123 responses from ESID members (23·7%) were, in the majority, very similar to those of AAAAI respondents, with > 10% of their practice devoted to primary immunodeficiency. There were major differences between the responses of these two groups and those of the general AAAAI respondents whose clinical practice was composed of < 10% of PID patients. These differences included the routine use of intravenous immunoglobulin therapy (IVIg) for particular types of PIDs, initial levels of IVIg doses, dosing intervals, routine use of prophylactic antibiotics, perceptions of the usefulness of subcutaneous immunoglobulin therapy (SCIg) and of the risk to patients' health of policies adopted by health-care funders. Differences in practice were identified and are discussed in terms of methods of health-care provision, which suggest future studies for ensuring continuation of appropriate levels of immunoglobulin replacement therapies.